Development of a Hydrogel loaded with Antibacterial Psidium guajava leaf extract - Atazar, Ronald Gian G.; Calimlim, Caryll Joy F. Dollano
Hydrogels, with their high-water content and biomimetic properties, are promising materials for wound dressings due to their ability to deliver therapeutic agents. Guava leaves (Psidium guajava) have a long history of traditional use in the Philippines for wound cleansing due to their perceived antibacterial activity. This study aimed to develop a hydrogel loaded with Psidium guajava leaf extract and evaluate its characteristics, including antibacterial activity, for potential wound dressing application. Ethanolic and aqueous leaf extract were prepared by maceration and decoction method respectively. The aqueous extract, with a brown color like the skin tone and antibacterial activity against S. aureus and P. aeruginosa as confirmed by TLC Bioautography and disk diffusion assay was chosen for hydrogel formulation. Pre-formulation studies assessed compatibility with excipients. Formulated hydrogels were evaluated for organoleptic properties, porosity, swelling, gel fraction, and antibacterial activity. The aqueous extract displayed a "strong" zone of inhibition against S. aureus but not against P. aeruginosa. Formulated hydrogels absorbed ethanol and phosphate buffer solution indicating porous characteristics. Interestingly, a hydrogel with moderate extract concentration (2.5 mg/mL) and higher porosity (54.17 ± 10.75%) exhibited the highest zone of inhibition among all formulations (12.00 ± 2.64 mm) against S. aureus, suggesting a potential role of porosity in extract release. This study successfully formulated a hydrogel loaded with P. guajava leaf extract that demonstrates antibacterial activity against S. aureus and possessed acceptable organoleptic properties intended for topical drug delivery, highlighting its potential for wound dressing applications. Further studies of the formulation to achieve optimal porosity and antibacterial activity are recommended. Additionally, exploration of activity against a broader range of microorganisms and alternative microbial testing methods is warranted.